ANALYSIS OF INTERNATIONAL LEGAL NORMS ESTABLISHING LIABILITY FOR CERTAIN OFFENSES AGAINST MORALITY, SUCH AS MAINTAINING A BROTHEL OR ENGAGING IN PROSTITUTION - Khudayberdiev Abdurashid Abdirasulovich; Ergashov Olimkhon Alisherovich (The Conference Hub, 2025)
One of the most important directions in the current stage of democratic renewal in our country is to strengthen the rule of law and legality, consistently democratize and liberalize the judicial and legal system aimed at reliably protecting the rights and interests of individuals. In a nutshell, further improving the foundations of a legal state and raising the legal awareness and culture of the population remain decisive tasks for us. Despite the existence and diversity of state borders, the interconnections between countries within a single international community are growing. International relations have a significant impact not only on the lives of states but also on each individual. The initial steps to combat maintaining brothels or pimping were taken in the late 19th century. Efforts to combat the exploitation of women and children for prostitution purposes began in the form of bilateral agreements (e.g., between Germany and the Netherlands in 1889, and between Germany and Austria in 1990). These issues were later discussed at the 1889 International Congress in London and the 1902 Conference in Paris, leading to the adoption of International Conventions on curbing the trafficking of women and children (1910, 1921, and 1933).